Concept, signal design, and measurement studies of the R‐mode Baltic system. Issue 3 (10th September 2021) - Bronk, Krzysztof; Koncicki, Patryk; Lipka, Adam; Niski, Rafał; Wereszko, Błażej
Abstract: This article presents the work conducted in the R‐Mode Baltic project, which aims to launch the R‐Mode demonstrator in the Baltic Sea area. The article describes the concept of the Automatic Identification System (AIS) infrastructure and VHF Data Exchange System (VDES) signal utilization with respect to their potential role in the future R‐Mode System. It also contains the analysis of the distance determination accuracy in the designed system based on calculation of the correlation between the received signal and the known transmitted signal, as well as the achievable ranges for various system configurations. Additionally, the paper discusses the implementation of the test‐bed transmitter and receiver, the methodology of measurement campaigns carried out in the Baltic Sea on the Gdynia‐Karlskrona route, as well as the obtained results. The collected measurement results were thoroughly analyzed and compared with theoretical values. The summary contains conclusions, as well as the plans for the next phase of measurement research.